2000
DOI: 10.1289/ehp.00108s2323
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating noncancer effects of trichloroethylene: dosimetry, mode of action, and risk assessment.

Abstract: Alternatives for developing chronic exposure limits for noncancer effects of trichloroethylene (TCE) were evaluated. These alternatives were organized within a framework for dose-response assessment-exposure:dosimetry (pharmacokinetics):mode of action (pharmacodynamics):response. This framework provides a consistent structure within which to make scientific judgments about available information, its interpretation, and use. These judgments occur in the selection of critical studies, internal dose metrics, phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 95 publications
0
38
0
Order By: Relevance
“…This highly fat-soluble compound is rapidly absorbed into the bloodstream, and has been shown to accumulate in the adipose (fat) tissue of humans and animals [1,2]. Known and suspected toxic effects of TCE and its metabolites in laboratory animals and/or humans include acute effects such as dizziness, drowsiness, headaches and fatigue, as well as chronic effects such as developmental defects and lung, kidney and liver tumors [3][4][5][6][7][8][9][10].…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
See 1 more Smart Citation
“…This highly fat-soluble compound is rapidly absorbed into the bloodstream, and has been shown to accumulate in the adipose (fat) tissue of humans and animals [1,2]. Known and suspected toxic effects of TCE and its metabolites in laboratory animals and/or humans include acute effects such as dizziness, drowsiness, headaches and fatigue, as well as chronic effects such as developmental defects and lung, kidney and liver tumors [3][4][5][6][7][8][9][10].…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…Transport of TCE between the capillary region and the other two adipose subcompartments (interstitial and adipocyte) is modeled in the PDE (10). The variables C B (t), C I (t) and C A (t) denote concentrations of TCE in the capillary, interstitial and adipocyte regions respectively, while C a (t) and C v (t) represent the systemic arterial and venous blood concentrations of TCE.…”
Section: Overview Of the Tce Modelmentioning
confidence: 99%
“…An association, but no direct cause-and-effect relationship, was found between elevated levels of chlorinated hydrocarbons, including TCE, and chromium in drinking water and congenital heart disease in children whose parents were exposed to this contaminated drinking water (16,17); follow-up studies in rats showed that TCE was a cardiac teratogen, but not a general teratogen during fetal organ development (18). An association between TCE exposure and cardiac anomalies and eye malformations has been found (18)(19)(20). Other studies, however, found no adverse reproductive effects in humans exposed to TCE in drinking water (12,21).…”
Section: Reproductive/developmental Effectsmentioning
confidence: 99%
“…Long-term exposure to TCE can result in hepatotoxicity, nephrotoxicity, and neurotoxicity, as reviewed by Bull (22), Lash (23), and Barton (20), respectively. Several studies in humans have investigated the relationship between TCE exposure and cancer.…”
Section: Cancer Riskmentioning
confidence: 99%
“…* The understanding of the mechanisms of carcinogenic action of TCE has improved. * The U.S. EPA has issued proposed revisions to its preferred methodology for conducting carcinogen risk assessment (10), which include procedures somewhat different than those used in previous agency analyses of TCE. Many of these developments are discussed more thoroughly in the accompanying stateof-the-science articles (6,9,(16)(17)(18)(19)(20) Together they raise a number of possibilities for new, more rigorous, and more biologically insightful analyses of whether and how much TCE may increase cancer risks in humans exposed to environmental concentrations.…”
mentioning
confidence: 99%